Structured Model of Tourism Attraction Development Based on 10A In the Sirah Kencong Natural Tourism Area, Blitar Regency, East Java - Earlike, Fitria; Sani, Anwar; Anam, Mochammad Musafa’ul (Proceedings of International Conference of Graduate School on Sustainability, 2022)
Blitar Regency is one of the National Tourism Development Areas (Kawasan Pengembangan Pariwisata Nasional) and has a superior natural tourist attraction, namely Kawasan Wisata Sirah Kencong which is included in the top ten best natural tourism areas in East Java. This area is located on the slopes of Mount Kelud and Mount Kawi with administrative boundaries covering two sub-districts, making this area have many tourist attractions, such as natural, cultural, and artificial tourism. Even though there are many tourist attractions, this has not been able to improve the welfare of the surrounding community. Therefore, this study aims to create a structured model using the 10A approach to create sustainable tourism to improve the welfare of the people around the area. The method used in this study is the ISM method involving 10 pentahelix stakeholders. The results of the research show that tourism development can be carried out through 1) integration of natural, cultural, and artificial tourism; 2) creating educational tourism activities; 3) area arrangement; 4) promotion; 5) accessibility improvements; 6) creating a new reservation/order procedure through digital media; 7) increase in the level of hospitality of the host; 8) making security and safety guarantees for tourists; 9) preparation of planning documents, and 10) regular monitoring and evaluation. Keywords: model; natural tourism; Sirah Kencong; tourist attraction